001 PP: ONLINE CLINICAL MANAGEMENT PATHWAYS FOR CHLAMYDIA TREATMENT: ENRICHING FORMATIVE EVALUATION OF A COMPLEX E-HEALTH INTERVENTION. Issue 4 (12th April 2015) - Aicken, CRH; Estcourt, CS; Gibbs, J; Sonnenberg, P; Mercer, CH; Tickle, L; Sutcliffe, LJ; Sadiq, ST; Shahmanesh, M
Abstract : Background: Novel online clinical management pathways for chlamydia (eSexualHealthClinic) are being developed, enabling people to receive treatment remotely from clinical settings, with minimal contact with healthcare-professionals. Development follows Medical Research Council complex interventions guidance, and is iteratively informed by qualitative research. In a mixed-methods pilot study, the eSexualHealthClinic is being explored for acceptability and preliminary evidence of effectiveness, among people who tested positive for chlamydia through conventional services. They receive test-results by text-message, and are offered online care. After completing an automated consultation, they can collect antibiotics from community pharmacies. If they prefer, or if medically appropriate, they are managed in clinic. Objective: To describe how the pilot study's qualitative component will deepen our understanding of its quantitative findings, further informing intervention development. Methods: Ongoing semi-structured follow-up telephone-interviews with people who used the eSexualHealthClinic, exploring views and experiences. Interviews are informed by the Theory of Planned Behaviour, also considering expectations and previous experiences of healthcare, emotional and contextual factors, themes from our previous qualitative research, and allowing emergent themes. Since prevention of transmission is paramount for infection control, reasons for delayed treatment are explored. Contribution of qualitative research: Interactions with the eSexualHealthClinic are time-logged, and participants are surveyed after completing care. These detailed quantitative data provide limited information on reasons for delays, (dis)satisfaction, and unmet needs. Qualitative research enables in-depth, contextualised exploration of these issues, including influences on care-seeking unanticipated by researchers, which cannot be examined quantitatively. Integration of qualitative and quantitative findings will enable participants' care-seeking behaviour to be more fully understood, informing care-pathway refinement, for maximum clinical and public health benefit. Discussion: Online healthcare is expanding. During development of novel web-based care-pathways, navigated with minimal supervision, understanding care-seeking behaviour through qualitative research is vital. This understanding is enhanced by mixed-methods design, where qualitative and quantitative research are mutually-enriching.